Camilla the cupcake fairy. - Bugbird, Tim.; Ede, Lara, illus (Nashville, TN : Make Believe Ideas, 2011)
Camilla the cupcake fairy is thrilled to get her very first wand, but when using it turns out to be more difficult than she expected she calls on her friends to help her.
Keywords: Fairies -- Fiction; Friendship -- Fiction; Stories in rhyme; Cupcakes -- Fiction